Intrinsic risk factors for the development of anterior knee pain in an athletic population. A two-year prospective study - Witvrouw, E.; Lysens, R.; Bellemans, J.; Cambier, D.; Vanderstraeten, G. (The American Journal of Sports Medicine, 2000)
Many variables have retrospectively been associated with the presence of anterior knee pain. Very few prospective data exist, however, to determine which of these variables will lead to the development of anterior knee pain. It was our purpose in this study to determine the intrinsic risk factors for the development of anterior knee pain in an athletic population over a 2-year period. Before the start of training, 282 male and female students enrolled in physical education classes were evaluated for anthropometric variables, motor performance, general joint laxity, lower leg alignment characteristics, muscle length and strength, static and dynamic patellofemoral characteristics, and psychological parameters. During this 2-year follow-up study, 24 of the 282 students developed patellofemoral pain. Statistical analyses revealed a significant difference between those subjects who developed patellofemoral pain and those who did not concerning quadriceps and gastrocnemius muscle flexibility, explosive strength, thumb-forearm mobility, reflex response time of the vastus medialis obliquus and vastus lateralis muscles, and the psychological parameter of seeking social support. However, only a shortened quadriceps muscle, an altered vastus medialis obliquus muscle reflex response time, a decreased explosive strength, and a hypermobile patella had a significant correlation with the incidence of patellofemoral pain. We concluded that the latter four parameters play a dominant role in the genesis of anterior knee pain and we therefore deem them to be risk factors for this syndrome.